Bolts, T-head, relieved shank, long thread, in heat resisting nickel base alloy NI-P101HT (Waspaloy), silver plated. Classification: 1210 MPa (at ambient temperature)/730°C. (15th June 1996) - British Standards Institution,
No abstract available